Unbuttoning the bachelor doc - Anders, Deanne (Harlequin medical romance., 2024)
Life has been one big bump in the road after another for midwife, Skylar. Moving to Nashville for a fresh start, she immediately clashes with grumpy bachelor, Dr Jared. So, she’s unimpressed when they must feature together on their patient’s reality TV show! On screen, they’re strictly professional. But off camera, she discovers there’s more to Jared than meets the eye. Can she convince this buttoned-up doc to let loose for once?